The Correlation of Santri’s Personal Hygiene to the Incidences of Scabies in Pesantren Al-Kautsar Simalungun (a boarding school) - Fanissa (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Background. Scabies is a skin disease caused by the parasite named Sarcoptes scabiei. Scabies commonly found in developing countries, including Indonesia. There is a high prevalence of scabies in children and adolescents. Scabies is an infectious disease influenced by either the presence or absence of risk factors for scabies in each individual. Scabies often occurs among people who live together. Objectives. This study intends to see whether there is an influence of personal hygiene behavior on the incidence rate of scabies. Method. This study is an observational analytic study with a cross-sectional design. Primary data were used in this study. The data were collected by doing history-taking, physical examination, as well as conducting ink tests on lesions on the patient's body to observes scabies, and interviews/questionnaires to observes personal hygiene behavior. The samples were chosen by a simple random sampling method. The data that has been collected will be analyzed using the fisher’s exact statistical test. Results. There are 91 respondents, including 39 men and 52 women with the age range of 12-15 years. Forty eight respondents (52,7%) are diagnosed scabies, 74 respondents (81,3%) have good personal hygiene, 17 of them (18,7%) have a bad personal hygieneConclusion. There is a significant correlation between personal hygiene and the incidence of scabies with p value of 0,001.